ALGORITHMIC TOOLS AND HEALTH CRISES. ETHICAL AND LEGAL ISSUES AND RECOMMENDATIONS - DELFIN ROSSARO, Alejandra; CHASSANG, Gauthier; RIAL-SEBBAG, Emmanuelle (MEDECINE LEGALE DROIT MEDICAL, 2025)
The use of algorithmic tools is becoming more and more widespread in public health crisis management policies. Put forward under the argument of making faster decisions based on a larger sample of data, they raise ethical questions related to the necessity, effectiveness and transparency of the tool, the equity and non-discrimination of individuals, and the respect for human dignity and autonomy. In the decision-making field, issues associated with algorithmic bias and nonrespect of privacy are also at stake. From examples of national and foreign public policies carried out during the period of the COVID-19 health crisis, we will study the impact of these algorithmic tools to conclude our work with a proposal of ethical recommendations.